Shorter Ground Contact Time and Better Running Economy: Evidence From Female Kenyan Runners. Issue 2 (February 2021) - Mooses, Martin; Haile, Diresibachew W.; Ojiambo, Robert; Sang, Meshack; Mooses, Kerli; Lane, Amy R.; Hackney, Anthony C.
Abstract : Abstract: Mooses, M, Haile, DW, Ojiambo, R, Sang, M, Mooses, K, Lane, AR, and Hackney, AC. Shorter ground contact time and better running economy: evidence from female Kenyan runners. J Strength Cond Res 35(2): 481–486, 2021—Previously, it has been concluded that the improvement in running economy (RE) might be considered as a key to the continued improvement in performance when no further increase in V[Combining Dot Above]O2 max is observed. To date, RE has been extensively studied among male East African distance runners. By contrast, there is a paucity of data on the RE of female East African runners. A total of 10 female Kenyan runners performed 3 × 1, 600-m steady-state run trials on a flat outdoor clay track (400-m lap) at the intensities that corresponded to their everyday training intensities for easy, moderate, and fast running. Running economy together with gait characteristics was determined. Subjects showed moderate to very good RE at the first (202 ± 26 ml·kg −1 ·km −1 ) and second (188 ± 12 ml·kg −1 ·km −1 ) run trials, respectively. Correlation analysis revealed significant relationship between ground contact time (GCT) and RE at the second run ( r = 0.782; p = 0.022), which represented the intensity of anaerobic threshold. This study is the first to report the RE and gait characteristics of East African female athletes measured under everyday training settings. We provided the evidence that GCT is associated with the superior RE of the female Kenyan runners.